Management of Technology and Innovation - Vijay Kumar Khurana (Ane Books Pvt Ltd., 2009)
In this modern era of high competition and fast changes, Technology and Innovation Management is assuming an ever increasing importance in shaping the progress and future of the nations and business firms. To be dynamic, change is a must and this phenomena is more pertinent with technology as it affects all aspects of life. With a whole new world of opportunities, it also brings new challenges and threats. Developments in the recent past have thus necessitated a fresh and serious look at Technology and Innovation Management for the entrepreneurs and managers, both present and future. This text book has been written for management and commerce students at the graduate and post graduate level. It largely meets the requirements of MBA program of GGS IP University for the subject â€œManagement of Technology, Innovation and Changeâ€ and should be highly useful for other programs of other universities as well. It is hoped that the book will be useful to the readers and provide them clarity on the subject.